Life Cycle and Suicidal Behavior among Women - Pablo Mendez-Bustos; Jorge Lopez-Castroman; Enrique Baca-García; Antonio Ceverino (The Scientific World Journal)
It is nowadays accepted that, independently of methodological issues, women commit fewer suicides than men but make more frequent attempts. Yet, female suicidal risk varies greatly along the lifetime and is linked to the most significant moments in it. A wide analysis of the existing literature was performed to provide a narrative description on the evolution of female suicidal rates from childhood to old age, considering the milestones in their life history. A detailed analysis of gender differences in suicidal behavior is key to establish preventive measures and priorities. More specific studies are needed to adapt future interventions on female suicide.